Tax noncompliance and insider trading - Kallunki, Juha-Pekka; Mikkonen, Jenni; Nilsson, Henrik; Setterberg, Hanna (Journal of Corporate Finance, 2016)
This paper explores whether insiders who have shown noncompliance with the tax law (‘noncompliant insiders’) are more prone to exploit their information advantage in insider trading, compared to other insiders (‘compliant insiders’). Our empirical results from analyzing archival data of all insider trades in Sweden show that noncompliant insiders use more of their information advantage to trade their insider stocks shortly before significant stock price changes, compared to compliant insiders. These results remain similar after controlling for various insider- and firm-specific determinants of insider returns, including firm and year fixed effects. We believe that our results are of interest for academics and regulatory authorities monitoring and screening insider trading activity.